Wages, Separations, and Job Tenure: On-the-Job Specific Training or Matching? - Mortensen, Dale T. (Journal of Labor Economics, 1988)
A general stochastic model of optimal job separation behavior is developed in the paper. The model nests both the job training and the job-matching hypotheses of the wage-tenure relationship as special cases. The purpose of the paper is to compare the implications of the two hypotheses for job turnover. That expected wealth-maximizing separation strategies are qualitatively identical under the two hypotheses is the principal theoretical result. Although the empirical implications of the two hypotheses for observations on the distribution of completed job-spell lengths are similar as a consequence, they are not quite identical.